Accessible and inclusive despite the pandemic situation (Confluenţe Bibliologice, 2020)
The role of the public library and the competencies of librarians have stepped into an experimental dimension, oriented towards training and knowledge exchange and become an essential tool in the educational approach, throughout life, both of the individual and of social groups as a whole. Libraries continue to fulﬁll their mission to provide access to information and documentary culture by resisting the complexity of their operation in this pandemic, in compliance with all health hygiene rules.
Keywords: modern library services; educational tools